2021
DOI: 10.3390/diagnostics11040734
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Abusive Head Trauma: A Systematic Review

Abstract: Abusive head trauma (AHT) represents a commonly misdiagnosed condition. In fact, there is no pathognomonic sign that allows the diagnosis in children. Therefore, it is such an important medico-legal challenge to evaluate reliable diagnostic tools. The aim of this review is to evaluate the current scientific evidence to assess what the best practice is in order to diagnose AHT. We have focused particularly on evaluating the importance of circumstantial evidence, clinical history, the use of postmortem radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…Any nonverbal child with concerns for NAT should have detailed neurologic evaluation, which includes a dilated fundoscopic exam by an ophthalmologist, to rule out abusive head trauma (AHT). Several studies have suggested that retinal hemorrhages are among the most reliable clinical features/predictors of AHT – present in 78% of cases (compared with 5% of accidental head injuries) [40]. These hemorrhages are usually extensive, bilateral, multilayered, and extend to the outer edges of the retinal pole when compared with retinal hemorrhages from accidental trauma.…”
Section: Nonaccidental Traumamentioning
confidence: 99%
See 1 more Smart Citation
“…Any nonverbal child with concerns for NAT should have detailed neurologic evaluation, which includes a dilated fundoscopic exam by an ophthalmologist, to rule out abusive head trauma (AHT). Several studies have suggested that retinal hemorrhages are among the most reliable clinical features/predictors of AHT – present in 78% of cases (compared with 5% of accidental head injuries) [40]. These hemorrhages are usually extensive, bilateral, multilayered, and extend to the outer edges of the retinal pole when compared with retinal hemorrhages from accidental trauma.…”
Section: Nonaccidental Traumamentioning
confidence: 99%
“…These hemorrhages are usually extensive, bilateral, multilayered, and extend to the outer edges of the retinal pole when compared with retinal hemorrhages from accidental trauma. Retinal hemorrhages have even been described in cases of AHT victims without radiographic signs of intracranial injury although this is rare [40,41]. Retinal hemorrhages and characteristic cutaneous features are key diagnostic components of the assessment of a child with NAT.…”
Section: Andandmentioning
confidence: 99%
“…According to Korean legal judgments, children who exhibit the SBS triad are considered victims of abuse even without a witness or a confession [4]. However, Elinder et al [5] argued that it is reasonable to diagnose a patient with SBS even without clear evidence of the triad, and several other studies have supported this claim [6][7][8][9][10]. Hoskote et al [6] investigated the association between non-accidental head injury in children with acute SDH and five risk factors: (1) RH; (2) age < 12 weeks; (3) inconsistent history; (4) positive skeletal survey; and (5) unexplained bruising.…”
Section: Introductionmentioning
confidence: 99%
“…AHT also accounts for 95% of all serious intracranial injuries and 64% of all head injuries in children [9]. Additionally, the presence of severe neurological symptoms along with SDH and RH is strongly suggestive of AHT in the child [10].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI), on the other hand, designates physical damage to brain tissue resulting from a bump, a jolt, or a blow to the head for a direct impact or rapid acceleration–deceleration [ 12 , 13 , 14 , 15 , 16 ]. It represents a leading cause of death, long-term impairment, disability, and poor quality of life worldwide, affecting millions of people throughout the world every year [ 17 ].…”
Section: Introductionmentioning
confidence: 99%